Penyelesaian Sengketa Pengalihan Piutang (Cessie) Syariah Di Peradilan Agama - Muqtadir, Samuel Mafatihul; Kamal, Muhammad; Abdullatif, Ahmad (Journal of Lex Philosophy (JLP), 2024)
Tujuan penelitian menganalisis proses penyelesaian sengketa pengalihan piutang (Cessie) Syariah di Peradilan Agama, (Studi Kasus Putusan MA RI. Nomor 881 K/Ag/2020); (2) Penerapan hukum secara tepat dan terperinci dalam pertimbangan hukum hakim Peradilan Agama pada sengketa pengalihan piutang (Cessie) Syariah, Penelitian ini menggunakan bahan-bahan bersumber dari Bahan hukum primer darn Bahan hukum sekunder, sebagai penjelasan mengenai bahan hukum primer. Hasil penelitian bahwa: (1) Proses administrasi perkara penyelesaian sengketa pengalihan piutang syariah di Peradilan Agama tersebut, secara umum telah sesuai Keputusan Ketua Mahkamah Agung RI., Nomor KMA/032/SK/IV/2006, dan Surat Edaran Mahkamah Agung RI., Nomor 2 Tahun 2014. (2) Pertimbangan hukum majelis hakim tingkat pertama menyalahi asas putusan wajib mengadili seluruh bagian gugatan terkait tuntutan serta merta, dan pertimbangannya kurang tepat terhadap obyek sita yang telah diikat hak tanggungan, dan terhadap pokok perkara pengalihan piutang, namun dipertimbangkan sebagai pengalihan utang. The research objective is to analyze the process of resolving disputes over the transfer of Sharia receivables (Cessie) in the Religious Courts, (Case Study of the Indonesian Supreme Court Decision. Number 881 K/Ag/2020); (2) Appropriate and detailed application of the law in the legal considerations of Religious Court judges in disputes regarding the transfer of Sharia receivables (Cessie). This research uses materials sourced from primary legal materials and secondary legal materials, as an explanation of primary legal materials. The research results show that: (1) The administrative process for resolving disputes over the transfer of sharia receivables in the Religious Courts, in general, is by the Decree of the Chairman of the Supreme Court of the Republic of Indonesia, Number KMA/032/SK/IV/2006, and the Circular Letter of the Supreme Court of the Republic of Indonesia., Number 2 of 2014. (2) The legal considerations of the panel of judges of the first level violate the principle of a decision that is obliged to try all parts of the lawsuit related to the claim immediately. The consideration is not appropriate for the confiscated object which has been tied to a mortgage, and for the subject matter of the transfer of receivables, but is considered as debt transfer.